Plant biotechnology and genetics : principles, techniques, and applications - Stewart, C. Neal, Jr. (Wiley, 2008)
* Provides a thorough overview of botany and genetics for those students with minimal background in those areas, with coverage extending from very basic introductory materials to advanced techniques and applications. * Includes autobiographical essays from eminent scientists to provide insight into the field of plant biotechnology and how it is changing the face of agriculture. * Facilitates group discussions on problems and issues in plant biotechnology through the use of chapter questions and problems. * Includes a CD ROM with colour graphics to aid students and teachers in presenting and un.